Measurements of a 5:1 blood pump model - Mohamad Haiqel Bin Jamaludin (2017)
This report presents the study of the flow behaviour of the fluid in the clearance gap of a scaled up model of the Kyoto-NTN Magnetically Suspended Centrifugal Blood Pump (MSCBP). The scales up model is 5 times by applying dimensional analysis. MSCBP was used among the other conventional ventricular assist devices as it has a lower haemolysis and thrombus formation. A hot wire anemometry is used in this study to measure the gap velocity in the clearance gap of 1mm in the scaled up model. Measurements of tangential and radial velocity at different radial and angular positions are taken. The angular positions are at intervals of 5 degrees for each measurement. The hot wire probe will also mounted at 3 different protrusion depths which are 0.25mm, 0.5mm, 0.75mm from the wall of the pump casing. The results of the tangential and radial velocity allow us to gain an understanding of the resultant velocity and the flow angle of the fluids for different depths. The results show that the tangential flow velocity plays a more significant role than the radial velocity in the flow behavior of the fluid. There was no re-circulation and the washout mechanism is more significant at the splitter plate at 180 degrees of angular position. This experimental study of the flow behavior can help in future studies of the blood pump and in optimizing it.